إنشاء تطبيق مساعدة المركبات المعطلة بنظام التموضع العالمي - العبادي مارية (university of eloued جامعة الوادي, 2024)
في عالمنا المتنقل و المتسارع، أصبحت الحاجة إلى كفاءة وفعالية خدمات المساعدة على الطريق أمرًا بالغ الأهمية.حيث تكمن اهميته في توفير السلامة الشخصية والاستاجابة السريعة والتواصل الفوري بين السائق والمسؤولين كما يعزز راحة بال المستخدم ويوفر خدمات محترفة ومنظمة مما يحسن من تجربة المستخدم . تواجه المركبات عدة مشاكل تقنية وحوادث مفاجئة على مستوى الطريق ,هنا يأتي تطبيقنا كحل لتوفير خدمات المساعدة للسائقين بتقنيات سريعة وكفاءة عالية , وذالك من خلال تحديد موقع المستخدم بدقة باستخدام نظام التموضع العالمي مع تقليل وقت الانتظار وزيادة رضا المستخدمين .سيعالج مشروعنا المشاكل التي تواجهها المركبات على الطريق ,وسيوفر حلولا سريعة وسهلة الاستخدام .تم استخدام إطار عمل Flutter Framework لتحقيق المشروع In our mobile and fast-paced world, the need for efficient and effective roadside assistance services has become extremely important, as its importance lies in providing personal safety, quick response, and immediate communication between the driver and officials. Lt also enhances the user’s peace of mind and provides professional and organized services, which improves the user experience. vehicles face several technical problems and sudden accidents on the road. Here comes an application as a solution to provide assistance services to drivers with fast technologies and high efficiency, by accurately determining the user’s location using the global positioning system while reducing waiting time and increasing user satisfaction. Our project will address the problems faced by vehicles on the road and will provide quick and easy-to-use solutions by using the flutter framework to achieve the project
مدكرة ليسانس اعلام الي
Keywords: خدمات المساعدة على الطريق، تحديد الموقع، نظام التموضع العالمي; Roadside Assistance; GPS; User Satisfaction